The impact of moderate and severe asthma exacerbations on quality of life: a post hoc analysis of randomised controlled trial data - Andrew Briggs; Shuaib Nasser; Eva Hammerby; Sarah Buchs; J. Christian Virchow (SpringerOpen, 2021)
Abstract Background This paper reports the duration of moderate and severe exacerbations in patients with house dust mite induced allergic asthma and the impact on patients' quality of life. Methods Post-hoc analyses were conducted using data collected during a phase III multi-national trial (MT-04) that investigated time to moderate or severe asthma exacerbation among 485 patients during withdrawal from inhaled corticosteroids. Patient diaries were analysed to ascertain duration of exacerbations. The impact on patients' quality of life was measured by calculating utilities for five health states using the EuroQol-5 Dimension (EQ-5D-3L) and Asthma Quality of Life Questionnaire (AQL-5D). A regression analysis predicted the disutility of moving from 'well controlled asthma' to the other four health states: 'partially controlled asthma', 'uncontrolled asthma', 'moderate exacerbation' and 'severe exacerbation'. Results Two hundred four patients experienced exacerbations. Moderate and severe exacerbations involved statistically significant reductions in lung function compared to the constant peak expiratory flow observed for patients without exacerbations. Lung function decline occurred for 28 days, decreasing approximately 14 days before an exacerbation followed by a return to baseline over 14 days. Asthma symptoms, the use of short-acting β2-agonists, and frequency of nocturnal awakening all increased, starting 10-14 days before an exacerbation, and returned to baseline within 10-28 days following exacerbations. Compared to 'well controlled asthma', the disutility of having a 'moderate exacerbation' ranged from − 0.0834 to − 0.0921 (EQ-5D-3L) and from − 0.114 to − 0.121 (AQL-5D); and of having a 'severe exacerbation' from − 0.115 to − 0.163 (EQ-5D-3L) and from − 0.153 to − 0.217 (AQL-5D), depending on the length of the observation period. Conclusions The impact of moderate and severe exacerbations in house dust mite induced allergic asthma extends 14 days before and 28 days after the peak exacerbation event. The impact of exacerbations on patients' health-related quality of life (HRQoL) continues long after their occurrence.